A green approach to fast synthesis of reduced graphene oxide using alcohol for tuning semiconductor property. (December 2019) - Phukan, Palash; Narzary, Rewrewa; Sahu, Partha Pratim
Abstract: Reduced graphene oxide (rGO) has been focused on different application such as photovoltaic, energy storage and clinical instrumentation due to its unique chemical, electrical and optical properties. Proper synthesis of rGO is required to achieve these properties. Here, a green approach using alcoholic mediums has been introduced to reduce the oxygen content in rGO for enhancement of electrical properties. The rGO samples prepared using ethanol, methanol, 2-propanol and acetone as reducing agents were analyzed by various characterization. The reduction of oxygen functional groups using ethanol medium promises a synthesis of rGO with enhanced electrical conductivity due to the presence of more graphene domain. The ethanol reduced graphene oxide provides band gap of 3.13 eV and room temperature conductivity of 1.19 S/m showing the semiconducting property for application of electronics device.